Colecistostomía laparoscópica como manejo de colecistitis aguda: Colecistectomía laparoscópica diferida - navarro coto, jose francisco (2022)
Laparoscopic cholecystostomy is a surgical technique that should be evaluated in patients with complicated acute cholecystitis, for subsequently perform a laparoscopic cholecystectomy in a second stage (delayed). The case of a patient with complicated acute cholecystitis is presented, in a peripheral hospital 1 (low complexity), more than 3 hours away from the referral hospital. It begins with the usual minimally invasive approach, documenting a gallbladder with characteristics that made it one of high complexity; likewise, human and technological resources increased the possibility of conversion and future morbidity. Therefore, it was decided to perform a cholecystostomy, provide antibiotic coverage, defer the procedure and discharge patient. Six weeks later, elective laparoscopic surgery is scheduled, where a satisfactory surgical procedure is performed with excellent postoperative response.